Distribution of Bacterial Growth Activity in Flow-Chamber Biofilms - Sternberg, Claus (American Society for Microbiology, 1999)
In microbial communities such as those found in biofilms, individual organisms most often display heterogeneous behavior with respect to their metabolic activity, growth status, gene expression pattern, etc. In that context, a novel reporter system for monitoring of cellular growth activity has been designed. It comprises a transposon cassette carrying fusions between the growth rate-regulated Escherichia coli rrnBP1 promoter and different variant gfp genes. It is shown that the P1 promoter is regulated in the same way in E. coli and Pseudomonas putida, making it useful for monitoring of growth activity in organisms outside the group of enteric bacteria. Construction of fusions to genes encoding unstable Gfp proteins opened up the possibility of the monitoring of rates of rRNA synthesis and, in this way, allowing on-line determination of the distribution of growth activity in a complex community. With the use of these reporter tools, it is demonstrated that individual cells of a toluene-degrading P. putida strain growing in a benzyl alcohol-supplemented biofilm have different levels of growth activity which develop as the biofilm gets older. Cells that eventually grow very slowly or not at all may be stimulated to restart growth if provided with a more easily metabolizable carbon source. Thus, the dynamics of biofilm growth activity has been tracked to the level of individual cells, cell clusters, and microcolonies.